Foetal endangerment through alcohol intoxication under Polish law: Can a mother be held criminally responsible? - Ornowska, Alicja (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
After pregnant women and women giving birth had been found drunk in many Polish cities, the state prosecution accused women of committing an offence of exposing their new-born children to an immediate danger of the loss of life or a danger of sustaining grievous bodily harm. In the paper it is argued that under current Polish criminal law any foetal endangerment is not criminalized as long as it is caused by the mother of a child. This also includes maternal consumption of alcohol during pregnancy. The issue in question is analyzed from the constitutional and criminal law dimension with axiological and comparative remarks and proposals as to the law amendments.
Keywords: zagrożenie płodu; prawa płodu; zatrucie alkoholem; uszkodzenie ciała